Immune Tumor Microenvironment in Breast Cancer and the Participation of Estrogen and Its Receptors in Cancer Physiopathology - Segovia-Mendoza, Mariana; Morales-Montor, Jorge (Frontiers in Immunology, 2019)
Breast cancer is characterized by cellular and molecular heterogeneity. Several molecular events are involved in controlling malignant cell process. In this sense, the importance of studying multiple cell alterations in this pathology is overriding. A well identified fact on immune response is that it can vary depend on gender. Steroid hormones and their receptors may regulate different functions and the responses of several subpopulations of the immune system. Few reports are focused on the function of estrogen receptors (ERs) on immune cells and their roles in different breast cancer subtypes. Thus, the aim of this review is to investigate the immune infiltrating tumor microenvironment and prognosis conferred by it in different breast cancer subtypes, discuss the current knowledge and point out the roles of estrogens and its receptors on the infiltrating immune cells, as well as to identify how different immune subsets are modulated after anti-hormonal treatments in breast cancer patients.